Fiqh and Contested Authorities: Rethinking the Role of Sole Mediator in Building the Non-Violent Religious Practices According to the Medina Charter - Pratama, Dito Alif (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The Medina Charter, also known as the Medina Constitution and was proposed by the Prophet Muhammad in 622 AD, is often regarded as one of the most important legal documents in Islamic history which provides an early example of peace building concepts in Islam, establishing the principles of governance, social relations, and religious tolerance in the early Muslim community. Based on a literature-review method, this paper, indeed, is an attempt to explore the performance of fiqh and its contested authorities which focuses on examining how far the role of a sole mediator (top-level approach) can prove to be effective in dealing with the issue of fiqh within disputing parties. The author contends that the Medina Charter provides a framework for establishing peace and harmony among various religious communities, and that the concept of a sole mediator is critical to accomplishing this goal. The article discusses the key provisions of the Medina Charter and their modern relevance, as well as how the role of a sole mediator can help to promote nonviolent religious practises and peaceful conflict resolution. The article reveals in its conclusion that the Medina Charter is indeed a relevant source of Islamic conception of reconciliation and peacemaking effort. This also evidences that use of non-violent approach by the sole mediator (top-level approach) in resolving the conflict, as is shown by Prophet Muhammad in Medina through the Medina Charter, was remarkably effective. It aides the construction of a peaceful social life age-old conflicts, developing bond of loves among the conflicting groups and restructuring the political power that were essential for developing sustainable peace in the Medina.Â Â